A 26.4-dB Gain 15.82-dBm 77-GHz CMOS Power Amplifier With 15.9% PAE Using Transformer-Based Quadrature Coupler Network - Chen, Liang; Zhang, Lei; Wang, Yan (IEEE microwave and wireless components letters, 2020)
This letter presents a novel compact power amplifier (PA) using the transformer-based quadrature coupler as the power splitter and combiner to achieve a large output power and high gain for automotive radar application. Compared with conventional transmission-line-based power splitter and combiner, the transformer-based quadrature coupler offers a low loss, wide bandwidth, and compact footprint. As a proof of concept, a 77-GHz PA is designed and implemented in a 65-nm CMOS technology. The measured small-signal power gain is 26.4 dB with a 8.5-GHz 3-dB bandwidth from 74 to 82.5 GHz. The measured P sat , OP 1 dB , and peak power added efficiency (PAE) are 15.82, 11.5 dBm, and 15.9%, respectively. In addition, the saturated output power at 77 GHz is 16.5 dBm at -40 °C and still remains as high as 13.5 dBm at 130 °C, which enables the automotive application. The proposed PA occupies a core area of 270 μm × 530 μm and the total dc power consumption is 240 mW.